Pedagogi Dialogis Yesus dalam Yohanes 4: Fondasi Etika Biblis bagi Pendidikan Pembebasan yang Keberlanjutan - Bofry Wahyu Samosir (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2026)
The dynamics of education in the 21st century still tend to be instrumental in nature, emphasizing only the transfer of knowledge and the preparation of workers for the market. As a result, this system fails to shape individuals into well-rounded human beings who have social and ecological responsibilities towards the world around them. This problem is also in line with Paulo Freire's criticism of the “banking concept of education,” which stifles critical consciousness. Faced with this problem, this article offers an alternative philosophy of education by recontextualizing the pedagogy of Jesus Christ in John 4 as a liberating and restorative educational paradigm. Specifically, through a hermeneutical approach, this article argues that Jesus' pedagogy, based on Christology Λόγος (Word), systematically breaks down the walls of gender and ethnic marginalization. The uniqueness of Jesus' dialogue with the Samaritan woman not only frees her from the shackles of social and religious marginalization as imago Dei, but also transforms her into an active agent of change. For the author, this process of personal liberation is an ethical prerequisite for the realization of personal responsibility towards others and nature. Thus, this article concludes that Jesus' dialogical pedagogy in John 4 is an ethical imperative that provides a biblical foundation for developing a framework of liberation education, leading to holistic sustainability practices. Therefore, as a form of contextualization, this pedagogical model provides a roadmap for educators, theologians, and ecologists to build collaborative networks in realizing concrete, sustainable, and just actions at the community level.AbstrakDinamika Pendidikan di abad ke-21 masih cenderung bersifat paradigma instrumental yaitu memberikan penekanan hanya pada aspek transfer pengetahuan, dan penyiapan tenaga kerja untuk pasar. Akibatnya sistem ini gagal membentuk setiap pribadi menjadi manusia utuh yang memiliki tanggung jawab secara sosial dan ekologis terhadap dunia di sekitarnya. Permasalahan ini juga sejalan dengan kritik Paulo Freire terhadap "konsep pendidikan gaya bank" yang melumpuhkan kesadaran kritis. Berhadapan dengan masalah ini, artikel ini hendak menawarkan sebuah alternatif filsafat pendidikan dengan merekontekstualisasi pedagogi Yesus Kristus dalam Yohanes 4 sebagai paradigma pendidikan yang memerdekakan dan memulihkan. Secara khusus, melalui pendekatan hermeneutika, artikel ini berargumen bahwa pedagogi Yesus, yang didasarkan pada Kristologi Λόγος (Sabda), secara sistematis mendobrak tembok marginalisasi gender dan etnis. Kekhasan dialog Yesus dengan Perempuan Samaria ternyata tidak hanya membebaskan perempuan Samaria dari belenggu marginalisasi sosial dan religius sebagai imago Dei, tetapi juga mentransformasinya menjadi seorang agen perubahan yang aktif. Bagi penulis, proses pembebasan personal inilah yang menjadi prasyarat etis bagi terwujudnya tanggung jawab pribadi terhadap sesama dan alam. Dengan demikian, artikel ini menyimpulkan bahwa pedagogi dialogis Yesus dalam Yohanes 4 merupakan sebuah imperatif etis yang menyediakan fondasi biblis untuk membangun sebuah kerangka pendidikan pembebasan yang mengarah pada praksis keberlanjutan yang holistik. Maka, sebagai bentuk kontekstualisasinya, model pedagogis ini memberikan sebuah peta jalan bagi para pendidik, teolog, dan pegiat ekologi untuk membangun jejaring kolaboratif dalam mewujudkan aksi nyata berkelanjutan yang berkeadilan di tingkat komunitas tertentu.